Role of echocardiography to avoid misclassification of pulmonary hypertension associated with left heart disease as precapillary pulmonary hypertension. (14th October 2021) - Janssen, B; Trujillo, P; Grignola Rial, J
Abstract: Background: The proportion of patients (pts) diagnosed with pulmonary arterial hypertension (PAH) at a more advanced age and/or with more risk factors for left ventricular diastolic dysfunction is increasing. Therefore, it can be challenging to differentiate PH associated with left heart disease (PH-LHD, PHpost) from other precapillary forms of PH (PHpre). Purpose: We analyzed the performance of the Opotowsky (OS), D'Alto (DS), and simplified D'Alto (sDS) echocardiographic scores according to the pretest probability (before right heart catheterization – RHC) of PH-LHD in pts with suspected PH submitted to RHC to identify the hemodynamic phenotype. Methods: 37 consecutive stable pts (3/2018–3/2020) with a tricuspid regurgitation peak velocity >2.8 m/s were prospectively included (21F, 49±17 yrs). Blinded transthoracic echocardiography was performed within 2 hours of RHC. We assessed OS (−2 to 2 points) and DS/sDS (0 to 34/7 points). We estimated cardiac index (thermodilution) and hemodynamic parameters using standard formulas. If PA occlusion pressure (PAOP) cannot properly be measured at end-expiration, we assessed left ventricular end-diastolic pressure (LVEDP). PH was defined as a mean PA pressure (mPAP) ≥25 mmHg. PAOP/LVEDP >15 mmHg defined PHpost. If the PAOP/LVEDP was between 13–15 mmHg in an I pt, a volume challenge was done. We categorized pts according to the pretest probability of PH-LHD proposed in the 6th WSPH based on the combination of 7 noninvasive variables (age, presence of CV comorbidities, presence of current or paroxysmal atrial fibrillation, prior cardiac intervention, presence of structural LHD, presence of left bundle branch/LV hypertrophy or RV strain in ECG, presence of left atrial dilatation/grade >2 mitral flow in Echo). The individual average probability was calculated by assigning a score of 1, 2, and 3 for each variable (1 = low (L), 2 = intermediate (I), and 3 = high (H) probability) rounding the average of the sum of values allocated for each variable to the nearest integer. Nonparametric ROC plots assessed the performance of echo-scores. Results: All pts had PH. 19 pts showed PHpost, 10/19 with PVR >3Wu (Combined PHpost). All scores were lower in PHpost compared to PHpre pts (p<0.05) (Table 1). ROC area was >0.9 with a similar Youden index (0.83) among the three scores (p<0.05) (Figure 1). 17 PHpost with H pts were correctly identified by all scores (94–100%). In 15 PHpre with L pts OS performed better than DS/sDS (93 vs. 80%). In 3 PHpre and 2 PHpost with I pts, DS/sDS performed better than OS (100 vs. 80%). Conclusion: The use of simple echo-scores could facilitate the screening of the hemodynamic phenotype in pts with PH, regardless of the pretest probability of PH-LHD. D'Alto scores might have some advantage compared to OS to classify the intermediate pretest probability of PH pts correctly. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Centro Cardiovascular Universitario. Hospital de Clínicas. Facultad de Medicina. Universidad de la República